The effect of Fe3O4 concentration to photocatalytic activity of Fe3O4@TiO2-PVP core-shell nanocomposite. (July 2020) - Sunaryono, S; Fitriana, D R; Novita, L R; Hidayat, M F; Hartatiek, H; Mufti, N; Taufiq, A
Abstract: A study on the preparation of Congo red textile dyes using nanocatalysts, Fe3 O4 @TiO2 material, and Polyvinyl Pyrrolidone (PVP) has been successfully carried out. The preparation of these dyes is intended as a controller of the shape and size of particles and as a superior adhesive in solution. Fe3 O4 @TiO2 core-shell (FTP) nanocomposite was carried out by coprecipitation method. The Fe3 O4 nanoparticles were designed as cores that were synthesized from Cilacap iron sand, while TiO2 nanoparticles were selected as a shell through the synthesis of Titanium (III) chloride. Fe3 O4 @TiO2 core-shell nanocomposite is characterized using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR), and UV-Visible Spectroscopic (UV-Vis). Through XRD data analysis, the crystalline nano-phase composite of Fe3 O4 @TiO2 core-shell did not experience significant changes with the addition of Fe3 O4 concentration. The contribution of the addition of Fe3 O4 concentration can be observed in changes in sample grain size. The higher the concentration of Fe3 O4 is, the smaller the grain size of the samples produced, ranging between 6-9 nm and can increase the percentage of degradation of Congo red dyes. In addition, optimum degradation in UV-Vis characterization occurred in FTP 0.5 samples that reached 78.20% at minute 100. The photodegradation effect that occurs in Congo red dyes is caused by photocatalytic mechanisms.